Penapisan Aktinomiset Rizosfer Tanaman Liliaceae sebagai Agens Pengendali Hayati Fusarium oxysporum f. sp. cepae - Eka Wijayanti; Abdjad Asih Nawangsih; Efi Toding Tondok (Jurnal Fitopatologi Indonesia, 2022)
Screening of Liliaceae Rhizosphere Actinomycetes as Biological Control Agents of Fusarium oxysporum f. sp. cepaeFusarium basal rot caused by F. oxysporum f. sp. cepae is one of the major diseases of shallot in Indonesia. The use of biocontrol agents is one alternative method for controlling this disease. Actinomycetes isolates have the potential as biological control agents for F. oxysporum f. sp. cepae because of its ability to produce bioactive compounds. This study aims to evaluate and select actinomycete isolates with the ability to inhibit the growth of F. oxysporum f. sp. cepae and potentially promote the growth of shallot crops. The study was divided into four stages: i.e. isolation, selection, characterization, and identification of the potential isolates. Forty-three isolates of actinomycetes were successfully isolated from Liliaceae plants, and 14 isolates were selected based on the results of the biosafety test. Antagonism test showed that 14 isolates produced inhibition of F. oxysporum f. sp. cepae by 3.67%–53.67%. Among them,  13 isolates produced chitinase enzyme with a chitinolytic index of 0.31–1.38. Five selected isolates, i.e., ABF42, ABF59, ACF45, AEF35, and AEF45, were able to solubilize phosphate and produced IAA at the concentration range of 24.82–82.88 ppm, but only three isolates were able to grow on media without nitrogen. Based on the sequences of 16S rRNA, the five isolates were identified as Streptomyces rameus, S. lydicus, S. panaciradicis, S. seoulensis, dan S. fuscichromogenes.